Deepening The Role of Macroprudential Policy on Capital Outflows in Indonesia - Eka Febrianti Utami; Regina Niken Wilantari; Teguh Hadi Priyono (Journal of Social Research, 2024)
Foreign capital flows to EMEs have increased significantly since 2004. After falling sharply in 2008 due to the global crisis, foreign capital flows then increased sharply until 2013 and declined thereafter due to the influence of Fed tapering policy. The results of VECM testing on sample data 2013.Q1 - 2021.Q1 in Indonesia show that there is indeed an influence of macroprudential policy. The nature of macroprudential policy on capital outflows is only a buffer policy, so a combination of other economic mix policies is needed. The right policy forms can be in the form of triple intervention policy in the spot market, domestic non-deliverable forward (DNDF) market and SBN purchases from the secondary market.